The effect of lesson study on questioning skills: improving students' answers - Cumhur, Fatma; Güven, Bülent (Taylor & Francis Ltd, 2022)
This study aimed to examine the effect of lesson study in developing pre-service mathematics teachers' questioning skills in terms of improving high school students' answers. The sample consisted of four pre-service teachers (PTs) studying mathematics teaching in a state university in northern Turkey. The study adopted a case study design. The data were obtained from transcriptions of each pre-service teachers two-hour lessons that had performed before, during, and after lesson study. During data interpretation, first of all, the frequency of the probing, guiding, and clarifying questions that pre-service teachers asked according to the periods was calculated. Then, in order to identify the effectiveness of these questions in improving the students' answers, the dialogues of PTs with the students were examined and the attention was paid to how PTs reacted to students' answers and the questions they used. Findings displayed the effectiveness of lesson study in increasing the use of probing, guiding, and clarifying questions to improve students' answers, and that these questions were qualitatively more successful in improving students' answers in the lesson study and after lesson study periods. It was recommended that pre-service education should focus on theoretical and practical training to improve mathematics teachers' questioning skills.
Keywords: Lesson study; questioning; skills; improving students' answers; professional development; pre-service teacher; Thinking